Methodology for Systemic Geopolitical Analysis according to the Lakatosian model. - Ioannis Mazis (Global New Positioning: The Importance of Transatlantic Relations, Africa, Near East, Russia and Asia for Greece, 2017)
The absence of an epistemologically founded geopolitical analysis method that has been internationally observed was the motivation for writing the following contribution. The paper is divided into two parts: i) Definitions and Example analysis and ii) Determination of the Lakatosian Structure of the Systemic Geopolitical Analysis.